SIRPγ-CD47 Interaction Positively Regulates the Activation of Human T Cells in Situation of Chronic Stimulation - Dehmani, Safa; Nerrière-Daguin, Véronique; Néel, Mélanie; Elain-Duret, Nathan; Heslan, Jean-Marie; Belarif, Lyssia; Mary, Caroline; Thepenier, Virginie; Biteau, Kevin; Poirier, Nicolas; Blancho, Gilles; Haspot, Fabienne (Frontiers in Immunology, 2021)
A numerous number of positive and negative signals via various molecules modulate T-cell activation. Within the various transmembrane proteins, SIRPγ is of interest since it is not expressed in rodents. SIRPγ interaction with CD47 is reevaluated in this study. Indeed, we show that the anti-SIRPγ mAb clone LSB2.20 previously used by others has not been appropriately characterized. We reveal that the anti-SIRPα clone KWAR23 is a Pan anti-SIRP mAb which efficiently blocks SIRPα and SIRPγ interactions with CD47. We show that SIRPγ expression on T cells varies with their differentiation and while being expressed on Tregs, is not implicated in their suppressive functions. SIRPγ spatial reorganization at the immune synapse is independent of its interaction with CD47. In vitro SIRPα-γ/CD47 blockade with KWAR23 impairs IFN-γ secretion by chronically activated T cells. In vivo in a xeno-GvHD model in NSG mice, the SIRPγ/CD47 blockade with the KWAR23 significantly delays the onset of the xeno-GvHD and deeply impairs human chimerism. In conclusion, we have shown that T-cell interaction with CD47 is of importance notably in chronic stimulation.